Thermal degradation and spectroscopy characterizations of TPS/PBAT blends irradiated by Cobalt-60 source - Dione Pereira de Castro; Leonardo Gondim de Andrade e Silva (Brazilian Journal of Radiation Sciences, 2022)
This study aimed to prepare blends of natural polymers of TPS with PBAT by reactive extrusion with irradiation process, using the plasticizers (castor oil and glycerol) to evaluate the thermal and chemical properties. The blends were submitted to the irradiation process using a Cobalt-60 source at a 25 kGy dose and then characterized by FTIR and DSC analysis. According to the results obtained in the FTIR tests, the blends did not undergo chemical changes during the irradiation process and, thus, maintained their properties. In the DSC tests, it was observed that the blends F2 (castor oil) and F3 (castor oil and TWEEN® 80) showed higher values of heat flow for degradation than the samples F0 (glycerol) and F1 (glycerol and TWEEN® 80), probably due to the chemical interaction of castor oil and its constituents. There was no thermal variation in the irradiation process between blends F0 and F1 or F2 and F3. It was concluded that it is feasible to replace castor oil with glycerol in TPS/PBAT blends, and the irradiation using a Cobalt-60 source, not changed the final properties analyzed.